Identification of microplastics in white wines capped with polyethylene stoppers using micro-Raman spectroscopy. (30th November 2020) - Prata, Joana C.; Paço, Ana; Reis, Vanessa; da Costa, João P.; Fernandes, António José Silva; da Costa, Florinda Mendes; Duarte, Armando C.; Rocha-Santos, Teresa
Highlights: Suspected microplastics are present in white wines up to 5, 857 particles L −1 . Micro-Raman spectroscopy confirmed microplastic presence in all bottles except two. Median dimensions of microplastics were 26 × 122 µm. The blue laser (442 nm) in spectroscopy allowed better signal to noise ratio. A reduction in filtered volume is preferred to 15% H2 O2 treatment. Abstract: Beverages, often packaged in plastic, can be a source of microplastics in the human diet. In this study, an improved method for detection of microplastics in white wines capped with synthetic stoppers is explored. Visual quantification in the stereomicroscope or using Nile Red were excluded due to the small size of particles. Quantification in the optical microscope identified up to 5, 857 particles.L −1 but lacked chemical characterization. Finally, micro-Raman spectroscopy was used for the first time in complex beverages in the identification of microplastics particles in white wines, allowing identification of at least one synthetic particle for each bottle, except in two cases. Improvements included reduction in volume filtered, selection of aluminum oxide filters, selection of blue laser and lack of H2 O2 treatment. Using this method, identification of all particles present in small representative areas of the filter by micro-Raman spectroscopy will allow proper quantification of microplastics in complex beverage matrices.